Forging new pathways for research on language learning motivation - Raby Françoise (Journal of Language and Cultural Education, 2015)
Research on motivation in the field of applied linguistics seeks to better understand how and why learners become involved in learning activities and maintain their efforts in this regard. Dörnyei provided a seminal model drawing essentially from cognitive and social psychology (Dörnyei, 2001). In the wake of his reflection, and after investigating motivation in a range of academic contexts, we are now able to present our own model, which is dynamic, weighted, and polytomic (Raby, 2007). After presenting cognitive ergonomics as a new pathway for research in second language acquisition, we shall present the results of our investigations in foreign language learning motivation in technologically enhanced contexts, outlining major methodological difficulties pertaining to this sort of this grounded research.